2008
DOI: 10.1140/epjb/e2008-00041-1
|View full text |Cite
|
Sign up to set email alerts
|

Heat and fluctuations from order to chaos

Abstract: The Heat theorem reveals the second law of equilibrium Thermodynamics (i.e.existence of Entropy) as a manifestation of a general property of Hamiltonian Mechanics and of the Ergodic Hypothesis, valid for 1 as well as 10 23 degrees of freedom systems, i.e. for simple as well as very complex systems, and reflecting the Hamiltonian nature of the microscopic motion. In Nonequilibrium Thermodynamics theorems of comparable generality do not seem to be available. Yet it is possible to find general, model independent,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 83 publications
(181 reference statements)
1
46
0
Order By: Relevance
“…[47] and Section 4 below. 5 5 In Ref. [47] it was observed that small temperature gradients allow the cold thermostat to behave as "thermodynamically" as the hot thermostat.…”
Section: Hard Core and Harmonic Potentialsmentioning
confidence: 99%
“…[47] and Section 4 below. 5 5 In Ref. [47] it was observed that small temperature gradients allow the cold thermostat to behave as "thermodynamically" as the hot thermostat.…”
Section: Hard Core and Harmonic Potentialsmentioning
confidence: 99%
“…(2) the probability distribution µ has an "explicit" expression "similar to the equilibrium Gibbs distribution", [7]. (3) µ is concentrated on a 0 volume "attractor".…”
Section: Chaotic Hypothesis (Ch) Motions Developing On the Attractingmentioning
confidence: 99%
“…Conversely the analysis of the CH anf the fluctuation theorems has implications on the theory of turbulence, [29,7,14].…”
Section: The Relation Holds For Patterns Which Can Be Realized With Amentioning
confidence: 99%
See 2 more Smart Citations